ماضی کی مسلم حکومتیں : زوال کے اسباب اور عصری معنویت: Muslim Dynasties Historic Reasons of decline and current Scenario - Mahmood, Dr. Salma (Al-Amīr Research Journal for Islamic Studies, 2024)
Rise and fall is an integral part in the history of nations. The history of the Muslim Ummah is unique in the sense that Islam soon spread to four continents and apart from the rise and fall of governments; Muslims included some regions in their empire where they were the minority. It is a proof of the great tolerance of the Muslims that there has never been a region where a Muslim government has gained a majority after coming to power. However, the research is on what was the reason for some areas that were permanently excluded from Muslim rule the history of the last two thousand years is reviewed, this fact is as clear as day, whether it is Asia or Africa, Spain or India, Muslim or non-Muslim, the fall of large, stable and durable dynasties is a tragedy. There are some general reasons for the fall of the government, in which no one can escape. In this article, while discussing the general causes of decline, we will discuss the specific causes of the decline of Muslim dynasties. Because if we want to reform the situation, and with compassion and sincerity, we are asking for revival for the Ummah Muhammadiyah then it is necessary that we first look at ourselves and carefully examine the causes of decline in order to correct us so that further tragedies can be avoided Keywords: Muslim governments, decline, historical analysis, contemporary relevance, political instability, economic weakness, social factors, introspection.